24 CIMMYT advanced wheat lines with high yield potential, good grain quality and disease resistance. - CGIAR Research Program on Wheat (2019)
24 lines showed ideal parameters for the mechanized bakery industry in Mexico, therefore representing high potential for the wheat value chain in Mexico.